Mengekstrak Senyawa Bioaktif yang Terkandung pada Kulit Kayu Manis dan Mengidentifikasinya dengan Teknik Gas Chromatography – Mass Spectroscopy (GC-MS) - Marissa Rijoice; Horasdia Saragih (Jurnal Biologi dan Pembelajarannya (JB&P), 2022)
The bioactive compounds contained in cinnamon bark have been extracted. Extraction carried out using ethanol, methanol and water as solvents. The type of compound extracted identified by gas chromatography - mass spectroscopy (GC-MS) technique. From result the identification carried out, obtained as many as eight types of compounds, namely: using ethanol as solvent: (1) cinnamaldehyde, (2) bornylester of acrylic acid, (3) alpha-copaene, (4)Cumarine, and (5) methyl isoheptadecanoate; generated with using methanol as solvent: (6) trioctanoin and (7) 1-hydroxy-2,2-dimethyldecane; and that produced using water as a solvent is (8) 2,5-cyclooctadienol. of the eight Of these compounds, the most dominant is cinnamaldehyde. This shows that the bark Sweet has the main content, cinnamaldehyde. Because the main content is cinnamaldehyde, then cinnamon bark has the potential to be developed in the future as an ingredient herbs for, among others, as anti-diabetic and anti-viral therapy, due to cinnamaldehyde has the character of being able to lower blood sugar levels and is very attractive to weaken the virus. Keywords: Extract, bioactive compounds, cinnamon bark, Gas Chromatography, Mass Spectroscopy.